Formation of periodic interfacial misfit dislocation array at the InSb/GaAs interface via surface anion exchange - Jia, Bo Wen (2017)
The relationship between growth temperature and the formation of periodic interfacial misfit (IMF) dislocations via the anion exchange process in InSb/GaAs heteroepitaxy was systematically investigated. The microstructural and electrical properties of the epitaxial layer were characterized using atomic force microscope, high-resolution x-ray diffraction, transmission electron microscopy, and Hall resistance measurement. The formation of interfacial misfit (IMF) dislocation arrays depended on growth temperature. A uniformly distributed IMF array was found in a sample grown at 310 °C, which also exhibited the lowest threading dislocation density. The analysis suggested that an incomplete As-for-Sb anion exchange process impeded the formation of IMF on sample grown above 310 °C. At growth temperature below 310 °C, island coalescence led to the formation of 60° dislocations and the disruption of periodic IMF array. All samples showed higher electron mobility at 300 K than at 77 K.